2018
DOI: 10.14295/cs.v9i1.1425
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivator on physiological performance of tomato and onion seeds

Abstract: Vegetable seeds have high commercial value, in the field after sowed seeds were exposed to unfavorable environmental conditions capable of causing reductions in the yield. Thiamethoxam is a bio-activator that may confer tolerance to stresses. In this regard, we aimed to evaluate the influence of thiamethoxam in the physiological performance of four lots of tomato and onion seeds. Seeds were treated with five doses of thiamethoxam, 0.0; 0.2; 0.4; 0.6 and 0.8 ml of product per 1000 seeds. The effects of the seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The positive effects of thiamethoxam were also observed in tomato and onion seeds, where the use (0.5 and 0.6 mL per 1000 seeds) provided higher physiological performance and more vigorous seedlings under normal sowing conditions (Tunes et al 2018). Under water-stress conditions, Almeida et al (2009) observed that thiamethoxam stimulated the physiological performance of carrot (Daucus carota L.) seeds and seedlings.…”
Section: Discussionmentioning
confidence: 88%
“…The positive effects of thiamethoxam were also observed in tomato and onion seeds, where the use (0.5 and 0.6 mL per 1000 seeds) provided higher physiological performance and more vigorous seedlings under normal sowing conditions (Tunes et al 2018). Under water-stress conditions, Almeida et al (2009) observed that thiamethoxam stimulated the physiological performance of carrot (Daucus carota L.) seeds and seedlings.…”
Section: Discussionmentioning
confidence: 88%